A critical test to disentangle the role of overshooting and rotation in stars. Issue Volume 14:Issue S343(2019) (August 2018) - Costa, G.; Girardi, L.; Bressan, A.; Marigo, P.; Chen, Y.; Kanniah, B.; Lanza, A.; Rodrigues, T. S.
Abstract: We study the mixing in low-intermediate massive stars using eclipsing binaries. We compute stellar evolutionary models with a varying convective core overshooting parameter and different rotation rates. Using a Bayesian estimation method, we found that the coexistence of the two phenomena may be a reasonable explanation of the observed extra-mixing.